Siti Walidah's Thoughts on the Concept of Feminism and its Relevance to Islamic Education - Aldira, Syifa Ulha; Aguswan, Aguswan; Hakim, Rosniati (Program Pascasarjana UMSB, 2024)
Educational rights, because women at that time did not receive the same behavior. The presence of the character Siti Walidah provides enlightenment and refreshment for women to continue to hone their potential so that in the context related to feminism and gender, it gives rise to the same thoughts and awareness of women's educational rights. This research aims to analyze the concept of Siti Walidah's thought, the concept of feminism and the relevance of Siti Walidah's thought to feminism in Islamic education.This type of research is a library research using descriptive analysis method. Data through journals, supporting books, by paying close attention to the required thesis. To validate the validity of the data using library study techniques, analyzed using a descriptive model by examining theories, opinions and main ideas contained in books that support and are relevant to the problems discussed in the research. The results of this research explain that Siti Walidah's struggle in pioneering the women's movement in the educational aspect can be seen from Siti Walidah's contribution in the form of Feminism in Islamic Education, namely 1. Siti Walidah's thought concepts including; rejecting the adage of wong wadon iku suwarga nunut nerakene katut wong lanang, consistent thinking towards good deeds nahi ungkar, instilling the philosophy of seni ing pamrih which is in accordance with Islamic philosophy, namely sincerity in doing good deeds, as well as equal education for women which gave birth to educational institutions 2. Feminism is a movement demanding gender equality between men and women. 3. The relevance of Siti Walidah's thoughts to the concept of Feminism is clear in terms of equal rights to education for women so that women today have the freedom to experience the same things as men in education both in the public sphere and at large in society. Keyword :Siti Walidah tought; Feminism; Relevance; Islamic Education